2015
DOI: 10.1080/19443994.2014.953401
|View full text |Cite
|
Sign up to set email alerts
|

Microfiltration of high concentration black tea streams for haze removal using polymeric membranes

Abstract: Black tea used for RTD beverages suffers from an inherent haze problem affecting the appeal of products in terms of colour and appearance; the affect also diminishes health giving properties. Microfiltration of black tea streams up to 10.0 wt.% has been carried out in an attempt to remove this haze by way of a feasibility study for a unit operation to replace current alkali solubilisation methods which can be damaging to the product. The three commercial polysulfone membranes tested show superior haze removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…However, the increasing trend became slow when CFV increase from 0.30 m/s to 0.47 m/s. Similar phenomenon was found in black tea, apple juice and titanium white waste acid clarification (Argyle & Bird, ; Vladisavljevic et al, ; Zhao et al, ).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…However, the increasing trend became slow when CFV increase from 0.30 m/s to 0.47 m/s. Similar phenomenon was found in black tea, apple juice and titanium white waste acid clarification (Argyle & Bird, ; Vladisavljevic et al, ; Zhao et al, ).…”
Section: Resultssupporting
confidence: 75%
“…In this work, the optimized TMP was about 0.12 MPa and higher pressure resulted in severe membrane fouling. apple juice and titanium white waste acid clarification (Argyle & Bird, 2014;Vladisavljevic et al, 2003;Zhao et al, 2003).…”
Section: Influence Of Transmembrane Pressure (Tmp) To Steady Fluxmentioning
confidence: 99%
“…This assumes that any modification occurring on the surface also occurs inside the pores. Argyle et al [9] showed that the through-pore negative zeta potential decreased upon ethanol treatment of PSU membranes. This indicated that the effect may arise due to a thin film of alcohol remaining on pore walls, resulting in a shielding of the true pore surface charge and consequently a reduction in the streaming potential value.…”
Section: Flux Uplift and Wetting Modificationmentioning
confidence: 99%
“…Instant tea suffers from an inherent haze problem or tea cream formation which causes the loss of transparency, colour, taste and cup quality (Powell et al, 1993) which reduces consumer preference and affects physical and sensory attributes and biological activities (Youngmok & Stephen, 2012). The complexation of polyphenols by the association of their galloyl groups with limited solubility is said to be the cause for the tea cream formation (Argyle & Bird, 2015). Studies have shown that phenolic acids, tea catechins, and flavanol glycosides are involved in tea creaming and potassium and calcium ions activated the process.…”
Section: Introductionmentioning
confidence: 99%